Silver Complexes of N-Heterocyclic Carbenes as Anticancer Agents: A Review: Life Sciences-Medicinal Chemistry - B. Aher, Sainath; R. Inamdar, Poonam; Kulkarni, Mrunalini; V. Puri, Makarand; Parekh, Srushti; Bendre, Vasudev (International Journal of Life Science and Pharma Research, 2022)
This review covers the explanation of all the biological efficiencies of the N-Heterocyclic Carbenes (NHCs). Most of the reviews of NHCs focused on its chemical and physical applications, we have noted the properties, types and applications of metal complexes of NHCS. Our principle aim is to throw a light on the biological applications of the complexes. N heterocyclic carbenes (NHC) have been discovered in the 90's and have been marking an important place in organic chemistry. NHCs contain divalent carbon atoms. It is bound to at least one nitrogen atom. Presence of heteroatoms imparts them a wide range of electronic behavior. They create stable bonds and compounds making them excellent ligands in coordination chemistry. Silver metal complexes of organic ligands had been an interesting research area for the pharmaceutical researchers. Because of the electron donating ability of NHCs, the formation of Ag metal complexes had been pursued by many inorganic chemists and they were evaluated for various biological activities. Thus, in this review we have listed out the Ag-NHCs which have anticancer potential and its use as cytotoxic therapeutic agents. This article concludes with the basic concept that, how to design efficient Ag-NHCs in order to develop efficient, biologically active metal complex derivatives.